6-Shogaol enhances the anticancer effect of 5-fluorouracil, oxaliplatin, and irinotecan via increase of apoptosis and autophagy in colon cancer cells in hypoxic/aglycemic conditions - Marta Woźniak; Sebastian Makuch; Kinga Winograd; Jerzy Wiśniewski; Piotr Ziółkowski; Siddarth Agrawal (BMC, 2020)
Abstract Background The development and growth of colorectal cancer based on constitutive activation of numerous signaling pathways that stimulate proliferation and metastasis. Plant-derived agents excel by targeting multiple aspects of tumor progression. Previous investigations have shown that ginger derivatives- shogaols possess anti-cancer and anti-inflammatory effects. In the present study, we have examined the anti-cancer effects of 6-shogaol alongside with the most widely used chemotherapeutic agents/regimens in the tumor-like microenvironment conditions. Methods Cytotoxicity on two colon cancer cell lines (SW480 and SW620) was measured by MTT test. Apoptosisassay, immunocytochemical and Western blotting analysis for autophagy and apoptosis detection were performed. Results Here, we report that 6-shogaol by itself or in combination with chemotherapeutic agents/regimens exerted a cytotoxic effect on CRC cells. Cell death might be linked with the activation of autophagy and apoptosis-related pathways. In the tumor-like microenvironment, which is characterized by hypoxia and glucose starvation, 6-shogaol with chemotherapeutics is significantly more potent than conventional chemotherapy alone. Conclusions Collectively, our data suggest that the addition of 6-shogaol to established chemotherapeutic regimens could potentially be a remarkable therapeutic strategy for colorectal cancer.